The utility of standing armies as a means of defence in an advanced stage of civilization - Jemison, William H. (Dublin Statistical Society, 1855)
That there is no necessary connection between what are called "Peace Principles" and Political Economy, has been pointed out to us this session by Dr. Hancock. I have thought, however, that the particular notice of the subject of Standing Armies might be opportune. The present unhappy state of our foreign relations, and the erroneous views put forward by some who profess a regard for economic principles, have led me to attempt this notice. Mr. Cobden has spoken of "standing armies as the standing curse of the present generation." The curse, however, consists not in them, but in that which renders them necessary. In this respect, there is an analogy between the military and the medical profession. Were it not for the pains and weaknesses of the body, we should not need the aid of the one. Were it not for the violence and evil passions of mankind, we should not require the protection of the other.
Read February 19th, 1855
Keywords: Armies; Military defense; 314.15